Isolation, Characterization, Complete Structural Assignment, and Anticancer Activities of the Methoxylated Flavonoids from Rhamnus disperma Roots - Hamdoon A. Mohammed; Mohammed F. Abd El-Wahab; Usama Shaheen; Abd El-Salam I. Mohammed; Ashraf N. Abdalla; Ehab A. Ragab (Molecules, 2021)
Different chromatographic methods including reversed-phase HPLC led to the isolation and purification of three O-methylated flavonoids; 5,4’-dihydroxy-3,6,7-tri-O-methyl flavone (penduletin) (1), 5,3’-dihydroxy-3,6,7,4’,5’-penta-O-methyl flavone (2), and 5-hydroxy-3,6,7,3’,4’,5’-hexa-O-methyl flavone (3) from Rhamnus disperma roots. Additionlly, four flavonoid glycosides; kampferol 7-O-α-L-rhamnopyranoside (4), isorhamnetin-3-O-β-D-glucopyranoside (5), quercetin 7-O-α-L-rhamnopyranoside (6), and kampferol 3, 7-di-O-α-L-rhamnopyranoside (7) along with benzyl-O-β-D-glucopyranoside (8) were successfully isolated. Complete structure characterization of these compounds was assigned based on NMR spectroscopic data, MS analyses, and comparison with the literature. The O-methyl protons and carbons of the three O-methylated flavonoids (1–3) were unambiguously assigned based on 2D NMR data. The occurrence of compounds 1, 4, 5, and 8 in Rhamnus disperma is was reported here for the first time. Compound 3 was acetylated at 5-OH position to give 5-O-acetyl-3,6,7,3’,4’,5’-hexa-O-methyl flavone (9). Compound 1 exhibited the highest cytotoxic activity against MCF 7, A2780, and HT29 cancer cell lines with IC50 values at 2.17 µM, 0.53 µM, and 2.16 µM, respectively, and was 2–9 folds more selective against tested cancer cell lines compared to the normal human fetal lung fibroblasts (MRC5). It also doubled MCF 7 apoptotic populations and caused G1 cell cycle arrest. The acetylated compound 9 exhibited cytotoxic activity against MCF 7 and HT29 cancer cell lines with IC50 values at 2.19 µM and 3.18 µM, respectively, and was 6–8 folds more cytotoxic to tested cancer cell lines compared to the MRC5 cells.